Dawr al-Jazāʼirīyīn fī Khidmat al-Turāth al-ʻUmānī al-Maṭbūʻ: Abū Isḥāq Ibrāhīm Aṭfayyish Unmūdhajan - Yaṭṭū, ʻĀʼishah; Mashwāt, Ḥalīmah (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
The relationship between Oman and Algeria strikes its roots deep into history, and among its most tangible expressions is the part Algerian scholars played in bringing the Omani heritage into print. This paper treats that role, taking as its case study the Algerian scholar Abū Isḥāq Ibrāhīm Aṭfayyish, whose editing, prefacing and publishing work carried a substantial body of Omani writing to readers across the Islamic world at the moment when the movement to print Omani works was beginning. The paper falls within the conference theme of Omani publications across the regions of the world, and examines how this Algerian contribution shaped which Omani texts reached print, in what form, and with what effect on the circulation of the Omani scholarly heritage beyond Oman itself.
MHF-PRINT2018-001
Keywords: Abū Isḥāq Aṭfayyish; Omani heritage; Printing history; Algeria; Critical editing; Cultural exchange